1990
DOI: 10.1007/bf01268022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perfusion lung scanning and angiography in the estimation of vascular obstruction in acute pulmonary embolism

Abstract: To determine the relationships between perfusion scan defect and angiographic severity (Miller index) in acute pulmonary embolism, we analysed examinations obtained before and after thrombolytic therapy in 34 consecutive patients free from underlying cardiopulmonary disease. The overall agreement between the two techniques was excellent (r = 0.82; mean absolute difference = 2.8%), although when embolic involvement was extensive (greater than 50% angiographic obstruction), the perfusion scan moderately underest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 14 publications
0
61
0
2
Order By: Relevance
“…The percentage of vascular obstruction by perfusion scanning (PVOs) was then calculated as: PVOs (%) = (1-overall perfusion score) ×100 and a PVOs ≥50% was defined as severe PE. 18 The relation of the ECG and ECHO findings with age, the presence of syncope and PVOs was assessed in a subgroup analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of vascular obstruction by perfusion scanning (PVOs) was then calculated as: PVOs (%) = (1-overall perfusion score) ×100 and a PVOs ≥50% was defined as severe PE. 18 The relation of the ECG and ECHO findings with age, the presence of syncope and PVOs was assessed in a subgroup analysis.…”
mentioning
confidence: 99%
“…18 Briefly, each lobe was assigned a weight based on the regional distribution of pulmonary blood flow while in the supine position. For each lobe, a semi-quantitative perfusion score from 0 to 1 (0, 0.25, 0.5, 0.75 and 1) was estimated.…”
mentioning
confidence: 99%
“…In this study, PVOs were used to assess the severity of PTE, which was found to be a reliable method of assessing the per cent of pulmonary vascular obstruction [6]. It was found that patients with PVOs w50% had significantly higher concentrations of factor VIIIc.…”
Section: Discussionmentioning
confidence: 99%
“…The method used to calculate this percentage has been described previously by MEYER et al [6]. Each lobe was assigned a weight based on the regional distribution of pulmonary blood flow in the supine position: right lower lobe 25%, right middle lobe 12%, right upper lobe 18%, left lower lobe 20%, lingual 12%, and left upper lobe 13%.…”
Section: Assessment Of Pulmonary Vascular Obstructionmentioning
confidence: 99%
“…Six-view perfusion lung scans were obtained, and the defects were scored by use of an anatomic reference chart. 11,12 With this score, each lobe is assigned a weight based on the regional distribution of pulmonary blood flow. An estimation of remaining perfusion is made for each lobe from 0.0 (no perfusion), to 0.25, 0.50, 0.75, to 1.0 (normal perfusion).…”
Section: Primary Outcome Assessmentmentioning
confidence: 99%